Oxford student's Dictionary - Ruse, Christina
The Oxford Student's Dictionary is for intermediate to advanced learners of English. It has a particular focus on curricular vocabulary and includes the words you need to study other subjects such as Art, Computing, Science, Geography, History, Literature, Maths, Sport and much more.